2012
DOI: 10.1093/ckj/sfs046
|View full text |Cite
|
Sign up to set email alerts
|

Effect of continuous positive airway pressure on proteinuria in obstructive sleep apnea

Abstract: Obstructive sleep apnea (OSA) is common in patients with renal disease, and an association between OSA and proteinuria has been proposed. However, the effect on proteinuria of OSA treatment with continuous positive airway pressure (CPAP) is unknown. We experienced a case of severe OSA, where proteinuria was clearly improved after CPAP initiation without any changes of medication or body weight. The remarkable reduction of repetitive apnea and hypopnea by CPAP might ameliorate proteinuria by lessening renal hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Previous studies have mounting evidences of OSA accelerating diabetes nephropathy [ 19 , 27 ], and a small study and case report showed that CPAP treatment may improve proteinuria in diabetes patients [ 28 , 29 ]. There are many factors including sleep cycle and the renin-angiotensin-aldosterone system [ 30 , 31 ], intermittent hypoxia-induced endothelial dysfunction and artery stiffness [ 32 34 ], and renal tubular dysfunction-related nocturnal natriuresis [ 29 , 35 , 36 ] that may impact kidney function from OSA.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have mounting evidences of OSA accelerating diabetes nephropathy [ 19 , 27 ], and a small study and case report showed that CPAP treatment may improve proteinuria in diabetes patients [ 28 , 29 ]. There are many factors including sleep cycle and the renin-angiotensin-aldosterone system [ 30 , 31 ], intermittent hypoxia-induced endothelial dysfunction and artery stiffness [ 32 34 ], and renal tubular dysfunction-related nocturnal natriuresis [ 29 , 35 , 36 ] that may impact kidney function from OSA.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic oxygenation strategies include the administration of erythropoietin to increase hematocrit levels, apparatus to effect continuous positive airway pressure, and whole-body chambers to produce an environment of 100% oxygen. 81,83,87,[110][111][112]377,378 Artery narrowing is already routinely counteracted by renal angioplasty with or without stenting and the administration of vasoconstriction inhibitors that target the renin-angiotensin-aldosterone system. 49,[379][380][381] The targeting of vasoconstriction pathways controlled through vasopressin, endothelin, and voltage dependent calcium channels are in their infancy, as is the use of vasodilators such as arginine and kallikrein.…”
Section: A New Hypoxia Paradigmmentioning
confidence: 99%